Linear Algebra Assignment Solutions
VerifiedAdded on 2023/05/31
|13
|2638
|468
AI Summary
This document contains solutions to Linear Algebra assignments and problems. It includes topics such as basis of P2, orthogonal basis of P2, inner product, and more.
Contribute Materials
Your contribution can guide someone’s learning journey. Share your
documents today.
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/26e79670-6a03-43b1-8272-8181049aa261-page-1.webp)
Running head: ASSIGNMENT 1
Linear Algebra
Student Name
Institution
Linear Algebra
Student Name
Institution
Secure Best Marks with AI Grader
Need help grading? Try our AI Grader for instant feedback on your assignments.
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/19e202ff-b595-46cc-ab35-0c09b08f01cb-page-2.webp)
ASSIGNMENT 2
Question 1
Question 1(a)
Let B= { x2, x,1} et S = { x2+x,2x-1,x+1} be two basis of P2
Let iB and is be the coordinate map induced on P2
B= { x2, x,1} T: P2 ⟶ P2
S= S = { x2+x,2x-1,x+1}
B and S are two basis of P2
[T ]B , S = [ 1 2 0
−1 3 5
2 2 −2 ] = {xϵ R3| T x= 0}
[ 1 2 0
−1 3 5
2 2 −2 ] [ x1
x2
x3 ] = [ 0
0
0 ]
x1 - 2x2 = 0
x1 = 2 x2 ……………………. Equation (1)
- x1 +3 x2 +5 x3 = 0 ……………………… Equation (2)
2x1 + 2x2-2 x3 =0 ……………………….. Equation (3)
From Equation (1) and Equation (2)
-2 x2 +3 x2 +5 x3 = 0
x2 +5 x3 = 0
From Equation (1) and Equation (3)
4 x2 +2x2 -2 x3 = 0
6 x2 -2 x3 = 0
3 x2 - x3 = 0
Question 1
Question 1(a)
Let B= { x2, x,1} et S = { x2+x,2x-1,x+1} be two basis of P2
Let iB and is be the coordinate map induced on P2
B= { x2, x,1} T: P2 ⟶ P2
S= S = { x2+x,2x-1,x+1}
B and S are two basis of P2
[T ]B , S = [ 1 2 0
−1 3 5
2 2 −2 ] = {xϵ R3| T x= 0}
[ 1 2 0
−1 3 5
2 2 −2 ] [ x1
x2
x3 ] = [ 0
0
0 ]
x1 - 2x2 = 0
x1 = 2 x2 ……………………. Equation (1)
- x1 +3 x2 +5 x3 = 0 ……………………… Equation (2)
2x1 + 2x2-2 x3 =0 ……………………….. Equation (3)
From Equation (1) and Equation (2)
-2 x2 +3 x2 +5 x3 = 0
x2 +5 x3 = 0
From Equation (1) and Equation (3)
4 x2 +2x2 -2 x3 = 0
6 x2 -2 x3 = 0
3 x2 - x3 = 0
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/c645be96-aa6d-4f4f-a119-a6e5aed190cf-page-3.webp)
ASSIGNMENT 3
Therefore, x3 = 3 x2 = 3( x2
2 ¿
x3 = 3 x2
2
x2 = x1
2 ⟶ x1 (1, 1
2 , 3
2 )
Null ( [T ]B ,θ) = {c(1, 1
2 , 3
2 ) ; cϵ R }
Null [ T BS ] = Span
{( 1
1
2
3
2 ) }
To find I B (T ) ,
[ 1 2 0
−1 3 5
2 2 −2 ]3∗3 [ x1
x2
x3 ]3∗1
= [ x1+2 x2
−x1+3 x2 +5 x3
2 x1 +2 x2 −2 x3 ]
= x1
[ 1
−1
2 ] + x2
[ 2
3
2 ] + x3
[ 0
5
−2 ]
Thus
[ 0
5
−2 ] = −2 [ 1
−1
2 ] + 1 [2
3
2 ]
= x1
[ 1
−1
2 ] + x2
[ 2
3
2 ] - 2 x3
[ 1
−1
2 ] + x3
[2
3
2 ]
= ( x1 -2 x3)
[ 1
−1
2 ] + ( x2 + x3)
[2
3
2 ]
Therefore, x3 = 3 x2 = 3( x2
2 ¿
x3 = 3 x2
2
x2 = x1
2 ⟶ x1 (1, 1
2 , 3
2 )
Null ( [T ]B ,θ) = {c(1, 1
2 , 3
2 ) ; cϵ R }
Null [ T BS ] = Span
{( 1
1
2
3
2 ) }
To find I B (T ) ,
[ 1 2 0
−1 3 5
2 2 −2 ]3∗3 [ x1
x2
x3 ]3∗1
= [ x1+2 x2
−x1+3 x2 +5 x3
2 x1 +2 x2 −2 x3 ]
= x1
[ 1
−1
2 ] + x2
[ 2
3
2 ] + x3
[ 0
5
−2 ]
Thus
[ 0
5
−2 ] = −2 [ 1
−1
2 ] + 1 [2
3
2 ]
= x1
[ 1
−1
2 ] + x2
[ 2
3
2 ] - 2 x3
[ 1
−1
2 ] + x3
[2
3
2 ]
= ( x1 -2 x3)
[ 1
−1
2 ] + ( x2 + x3)
[2
3
2 ]
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/44298326-1c3d-482e-8803-18ad29594f95-page-4.webp)
ASSIGNMENT 4
I B (([T ])B , s) span {( 1
−1
2 ) , ( 1
3
2 ) }
Therefore,
(T BS)= Span {( 1
−1
2 ), (2
3
2 ), (0
5
2 ) }
Question 1(b)
T: M 3∗3 ⟶ P2
T
(a b c
d e f
g h i ) = (a-b) x2 +c(x-1)+d
T
(1 0 0
0 0 0
0 0 0 ) = x2
T
(0 1 0
0 0 0
0 0 0 ) = (-1) x2
T
(0 0 0
0 0 0
1 0 0 ) = 1(X-1)
T
(0 0 0
0 0 0
0 0 1 ) = 1
Now,
T
(a b c
d e f
g h 1) = 0, a=1, e=1,i=1 and b,c,d,f,g,h = 0
I B (([T ])B , s) span {( 1
−1
2 ) , ( 1
3
2 ) }
Therefore,
(T BS)= Span {( 1
−1
2 ), (2
3
2 ), (0
5
2 ) }
Question 1(b)
T: M 3∗3 ⟶ P2
T
(a b c
d e f
g h i ) = (a-b) x2 +c(x-1)+d
T
(1 0 0
0 0 0
0 0 0 ) = x2
T
(0 1 0
0 0 0
0 0 0 ) = (-1) x2
T
(0 0 0
0 0 0
1 0 0 ) = 1(X-1)
T
(0 0 0
0 0 0
0 0 1 ) = 1
Now,
T
(a b c
d e f
g h 1) = 0, a=1, e=1,i=1 and b,c,d,f,g,h = 0
Secure Best Marks with AI Grader
Need help grading? Try our AI Grader for instant feedback on your assignments.
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/b995d26d-4110-47dc-84e5-592d51a1e757-page-5.webp)
ASSIGNMENT 5
So the basis of Ker(T) = ( 1 0 0
0 1 0
0 0 1 )
And the basis of Image of T (Im(T) )
= {1,X, X2}
Question 2
We have shall check the following inner product for < , ∙ ,> ; let u,v,wϵ v and λ is a scalar then;
a) <u,v>1 =¿ T ( u ) , T ( v )> ¿
¿ T ( v ) ,T ( w ) >¿ ¿ ¿
= ¿ v , u>¿ ¿ [∵ <,> is an inner product on V]
b) <u+v,w>1 = ¿ T ( u+ v ) ,T ( w ) >¿
= ¿ T ¿
= ¿ T ¿
=<u,w>1 =+ <v,w>1
c) <λu+v>1 = ¿ T ( λu ) , T ( v ) >¿
= ¿ λT ¿ [∵ T is linear]
= ¿ T ¿
=<u,w>1 =+ <v,w>1
d)
<u,u>1 = <T(u),T(w) ≥ 0 and <T(u) , T(u)> = 0 iff T(u) = θ
where θis the null element of u=θ [∵ T is injective ]
so, <u,u> ≥ 0 for all v and <u,u>1 for all uϵ V and <u,u>1 = 0 iff u=0
hence <,>1 satisfies all axioms of inner product and it is a inner product on V
If T is positive definite matrix, then T will give n inner product
So the basis of Ker(T) = ( 1 0 0
0 1 0
0 0 1 )
And the basis of Image of T (Im(T) )
= {1,X, X2}
Question 2
We have shall check the following inner product for < , ∙ ,> ; let u,v,wϵ v and λ is a scalar then;
a) <u,v>1 =¿ T ( u ) , T ( v )> ¿
¿ T ( v ) ,T ( w ) >¿ ¿ ¿
= ¿ v , u>¿ ¿ [∵ <,> is an inner product on V]
b) <u+v,w>1 = ¿ T ( u+ v ) ,T ( w ) >¿
= ¿ T ¿
= ¿ T ¿
=<u,w>1 =+ <v,w>1
c) <λu+v>1 = ¿ T ( λu ) , T ( v ) >¿
= ¿ λT ¿ [∵ T is linear]
= ¿ T ¿
=<u,w>1 =+ <v,w>1
d)
<u,u>1 = <T(u),T(w) ≥ 0 and <T(u) , T(u)> = 0 iff T(u) = θ
where θis the null element of u=θ [∵ T is injective ]
so, <u,u> ≥ 0 for all v and <u,u>1 for all uϵ V and <u,u>1 = 0 iff u=0
hence <,>1 satisfies all axioms of inner product and it is a inner product on V
If T is positive definite matrix, then T will give n inner product
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/b7dae819-53b1-41f9-81f8-b795e45443cf-page-6.webp)
ASSIGNMENT 6
<f,g> = ∫
0
1
(f ( t ) −f ' ( t ) )( g ( t ) −g' ( t ) )dt
<f,f> = ∫
0
1
(f ( t )−f ' ( t ) )2 dt
If <f,f> = 0 ⟹ f ( t )−f ' ( t ) = 0
⟹ f ( t )=f ' ( t )
⟹ f ( t )=et ∀ t and f ϵ pn
But et ∉ pn thus not an inner product since <f,f> = 0 ≇ f = 0 hence false
Question 3
Question 3(a)
(f,g) = ∫
0
∞
e−t f(t)g(t) dt
P(x) = x3
The basis of P2 is {1,x,x2}
We need to determine the orthogonal basis of P2
Let
v1 = 1 ………………….. Equation 1
v2 = x ………………….. Equation 2
v3 = x3 ………………….. Equation 3
Therefore by Gram Schmidt orthogonalization process, we get
w1 =1 …………………………………… Equation 4
v1 = 1 ……………………………….. Equation 5
w2 = v2- (v2 , w1 )
(w1 , w1)…………………………..Equation 6
<f,g> = ∫
0
1
(f ( t ) −f ' ( t ) )( g ( t ) −g' ( t ) )dt
<f,f> = ∫
0
1
(f ( t )−f ' ( t ) )2 dt
If <f,f> = 0 ⟹ f ( t )−f ' ( t ) = 0
⟹ f ( t )=f ' ( t )
⟹ f ( t )=et ∀ t and f ϵ pn
But et ∉ pn thus not an inner product since <f,f> = 0 ≇ f = 0 hence false
Question 3
Question 3(a)
(f,g) = ∫
0
∞
e−t f(t)g(t) dt
P(x) = x3
The basis of P2 is {1,x,x2}
We need to determine the orthogonal basis of P2
Let
v1 = 1 ………………….. Equation 1
v2 = x ………………….. Equation 2
v3 = x3 ………………….. Equation 3
Therefore by Gram Schmidt orthogonalization process, we get
w1 =1 …………………………………… Equation 4
v1 = 1 ……………………………….. Equation 5
w2 = v2- (v2 , w1 )
(w1 , w1)…………………………..Equation 6
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/aa1f547d-478c-41a8-8c38-b7c854e118c5-page-7.webp)
ASSIGNMENT 7
From equation 1 and 2,
w2 = x- ( x ,1)
(1,1) .1
w2 = x- 1
(x,1) = ∫
0
∞
e−t .t.1 dt = [ −t e−t−e−t ] ∞
0 = 1
(1,1) = ∫
0
∞
e−t .1 dt = [ −e−t ] ∞
0 = 1
w3 = v3- ( v3 , v1)
( w1 , w1)* w1 - (v3 , w2 )
( w2 , w2)
= x2 – ( x2 ,1)
(1,1) - ¿ ¿(x-1)
Therefore,
¿) = ∫
0
∞
e−t .t2 dt= 0+2 = 2
¿) = ∫
0
∞
e−t .t2 (t−1) dt
= ∫
0
∞
t3 e−tdt - ∫
0
∞
t2 e−tdt
= 0+(3*2)-2
=4
(x-1,x-1) = ∫
0
∞
e−t .(t−1)(t−1) dt
= ∫
0
∞
e−t .(t2−2 t+1) dt
= 2-2+ [ e−t ] ∞
0
From equation 1 and 2,
w2 = x- ( x ,1)
(1,1) .1
w2 = x- 1
(x,1) = ∫
0
∞
e−t .t.1 dt = [ −t e−t−e−t ] ∞
0 = 1
(1,1) = ∫
0
∞
e−t .1 dt = [ −e−t ] ∞
0 = 1
w3 = v3- ( v3 , v1)
( w1 , w1)* w1 - (v3 , w2 )
( w2 , w2)
= x2 – ( x2 ,1)
(1,1) - ¿ ¿(x-1)
Therefore,
¿) = ∫
0
∞
e−t .t2 dt= 0+2 = 2
¿) = ∫
0
∞
e−t .t2 (t−1) dt
= ∫
0
∞
t3 e−tdt - ∫
0
∞
t2 e−tdt
= 0+(3*2)-2
=4
(x-1,x-1) = ∫
0
∞
e−t .(t−1)(t−1) dt
= ∫
0
∞
e−t .(t2−2 t+1) dt
= 2-2+ [ e−t ] ∞
0
Paraphrase This Document
Need a fresh take? Get an instant paraphrase of this document with our AI Paraphraser
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/ddadde27-8147-4ded-b0a2-5c953c91319a-page-8.webp)
ASSIGNMENT 8
=2-2+1
= 1
Therefore,
w3 = x2- 2
1- 4
1 (x-1)
= x2- 2−4 (x−1)
= x2-2-4x+4
= x24x+2
Thus, orthogonal basis of P2 IS {1,x-1, x24x+2}
Orthogonal projection of P(x) = x3 onto P2 = Projw1P(x) Projw2P(x)+Projw3P(x)
= ( P ( x ) , w1)
( w1 , w1 ) w1 + ( P ( x ) , w2)
(w2 , w2 ) w2+( P ( x ) , w3)
( w3 , w3 ) w3
(P ( x ) , w1) = ( x3, 1)
= ∫
0
∞
e−t .t3 dt
= 0+(3*2)
= 6
(P ( x ) , w2) = ( x3, x-1)
= ∫
0
∞
e−t .t3 (t−1)dt
= ∫
0
∞
e−t t4dt - ∫
0
∞
e−t t3dt
= 0+(24-6)
= 18
(P ( x ) , w3) = (x3, x2−4 x+2)
=2-2+1
= 1
Therefore,
w3 = x2- 2
1- 4
1 (x-1)
= x2- 2−4 (x−1)
= x2-2-4x+4
= x24x+2
Thus, orthogonal basis of P2 IS {1,x-1, x24x+2}
Orthogonal projection of P(x) = x3 onto P2 = Projw1P(x) Projw2P(x)+Projw3P(x)
= ( P ( x ) , w1)
( w1 , w1 ) w1 + ( P ( x ) , w2)
(w2 , w2 ) w2+( P ( x ) , w3)
( w3 , w3 ) w3
(P ( x ) , w1) = ( x3, 1)
= ∫
0
∞
e−t .t3 dt
= 0+(3*2)
= 6
(P ( x ) , w2) = ( x3, x-1)
= ∫
0
∞
e−t .t3 (t−1)dt
= ∫
0
∞
e−t t4dt - ∫
0
∞
e−t t3dt
= 0+(24-6)
= 18
(P ( x ) , w3) = (x3, x2−4 x+2)
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/bd193d61-3550-4431-9cab-b15d54f1f85b-page-9.webp)
ASSIGNMENT 9
= ∫
0
∞
e−t .t3 (t2 −4 t +2)dt
= (0+5∗18)-(4*18+12)
= 0+(24-6)
= 18+12
= 30
(w3 , w3 ¿ = ∫
0
∞
e−t .(t2−4 t+2)(t2−4 t+2)dt
= ∫
0
∞
e−t .¿-8t +2t2 -8t +4t) dt
= ∫
0
∞
e−t .¿-8t +2t2 -8t +4t) dt
= ∫
0
∞
e−t .¿) dt
= 24-8*6+20*2-16*1+4
= 4
Therefore, orthogonal projection of P(x) = x3 onto P2 is
= 6*1+18 w2 + 30
4 w3
= 6+18(x-1)+ 15
2 ¿ ¿ -4x+2)
= 6+18x-18+ 15
2 x2 -30x+15
= 15
2 x2 -12x+3
Question 3(b)
∈ = {f*(P2|f(0) = 0}
= ∫
0
∞
e−t .t3 (t2 −4 t +2)dt
= (0+5∗18)-(4*18+12)
= 0+(24-6)
= 18+12
= 30
(w3 , w3 ¿ = ∫
0
∞
e−t .(t2−4 t+2)(t2−4 t+2)dt
= ∫
0
∞
e−t .¿-8t +2t2 -8t +4t) dt
= ∫
0
∞
e−t .¿-8t +2t2 -8t +4t) dt
= ∫
0
∞
e−t .¿) dt
= 24-8*6+20*2-16*1+4
= 4
Therefore, orthogonal projection of P(x) = x3 onto P2 is
= 6*1+18 w2 + 30
4 w3
= 6+18(x-1)+ 15
2 ¿ ¿ -4x+2)
= 6+18x-18+ 15
2 x2 -30x+15
= 15
2 x2 -12x+3
Question 3(b)
∈ = {f*(P2|f(0) = 0}
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/0fb5b44f-51ec-425c-8268-a4b8a50f43e6-page-10.webp)
ASSIGNMENT 10
Let a+bx+(x2+a x3 ∈ E)
⟹ a+b(0) +c(0)2 +d(0)3-E
a+b(0) +c(0)2 +d(0)3-E = 0
a=0
Therefore, the elements of the form +( x2+a x3 ∈ E) and it is spanned by x, x2, x3 . Therefore basis
of E is (x,x2, x3) .
Question 4
Question 4
In order to prove u0 is unique in T(v) = < u0 , v> ∀ r ϵ v
Let u0 is not unique ⟹ T(v) = < u0 , v>
T(v) = < u1 , v>
⟹ < u0 , v> = < u1 , v>
⟹ < u0-u1, 0> = 0
So by property of inner product ⟹ u0-u1 (u0=u1) hence u0 is unique
Now to find qϵ p2 ∀ P ϵ P2
P(0) = ∫
−1
1
q (t)p(t) dt
Let q(t) = A+Bt+C t2
P(0) = ∫
−1
1
( A +Bt +C t2)p(t) dt
Let P(t) = 1 ⟹ P2 ( x) ⟹ 1 = ∫
−1
1
( A +Bt +C t2) dt
1= 2A+ 2C
3 ……………………………………………. Equation 1
Let a+bx+(x2+a x3 ∈ E)
⟹ a+b(0) +c(0)2 +d(0)3-E
a+b(0) +c(0)2 +d(0)3-E = 0
a=0
Therefore, the elements of the form +( x2+a x3 ∈ E) and it is spanned by x, x2, x3 . Therefore basis
of E is (x,x2, x3) .
Question 4
Question 4
In order to prove u0 is unique in T(v) = < u0 , v> ∀ r ϵ v
Let u0 is not unique ⟹ T(v) = < u0 , v>
T(v) = < u1 , v>
⟹ < u0 , v> = < u1 , v>
⟹ < u0-u1, 0> = 0
So by property of inner product ⟹ u0-u1 (u0=u1) hence u0 is unique
Now to find qϵ p2 ∀ P ϵ P2
P(0) = ∫
−1
1
q (t)p(t) dt
Let q(t) = A+Bt+C t2
P(0) = ∫
−1
1
( A +Bt +C t2)p(t) dt
Let P(t) = 1 ⟹ P2 ( x) ⟹ 1 = ∫
−1
1
( A +Bt +C t2) dt
1= 2A+ 2C
3 ……………………………………………. Equation 1
Secure Best Marks with AI Grader
Need help grading? Try our AI Grader for instant feedback on your assignments.
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/6c4cbf30-a13c-42f3-8515-98ac9cc74f91-page-11.webp)
ASSIGNMENT 11
P(t) = t ⟹ 0 = ∫
−1
1
( At + B t2+C t3 )dt
P(0) = 0 ⟹ 0 = 0+ 2 B
3 +0 ⟹ B=0 ……………………. Equation 2
Let P(t) = t2 ⟹ P2
P(0) = 0
0 = ∫
−1
1
( A t 2 +B t3 +C t4 )dt
0 = 2A ( t3
3 )
'
+0 +2C( t5
5 )
'
0 = 2 A
3 + 2C
3 = 0 ⟹ 5A = -3C ………………. Equation 3
From equation 1,
1= 2 A+ 2C
3
⟹ 1= −8
15 C
C= −15
8
A= 9
8
Therefore,
q(t) = 9
8 + 0.t- 15
8 t2
q(t) = 9
8 - 15
8 t2
Question 5
Question 5(a)
P(t) = t ⟹ 0 = ∫
−1
1
( At + B t2+C t3 )dt
P(0) = 0 ⟹ 0 = 0+ 2 B
3 +0 ⟹ B=0 ……………………. Equation 2
Let P(t) = t2 ⟹ P2
P(0) = 0
0 = ∫
−1
1
( A t 2 +B t3 +C t4 )dt
0 = 2A ( t3
3 )
'
+0 +2C( t5
5 )
'
0 = 2 A
3 + 2C
3 = 0 ⟹ 5A = -3C ………………. Equation 3
From equation 1,
1= 2 A+ 2C
3
⟹ 1= −8
15 C
C= −15
8
A= 9
8
Therefore,
q(t) = 9
8 + 0.t- 15
8 t2
q(t) = 9
8 - 15
8 t2
Question 5
Question 5(a)
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/57342584-c182-4148-9de9-ba4eb1824da8-page-12.webp)
ASSIGNMENT 12
Given, A= [ 3 2 2
2 3 2
2 2 3 ]
The characteristic equation of A is, |3−x 2 2
2 3−x 2
2 2 3−x|x=0
i.e (3-x)*[(3−x)2−4] – 2*[6-2x-4] +2*[4-+2x] = 0
(3-x)*[5−6 x+ x2] + 8x -8 =0
x3 - 9x2 +15x -7 =0
(x−1)2 (X-7) = 0
X= 1, 1, 7
Thus the Eigenvalues of A are 1, 1, and 7 then the Eigenvectors are given as:
c
[
−1
1
0 ] +d [−1
0
1 ] Where c, d ≠ 0
The corresponding Eigenvector to the above Eigenvalue 7 is :
c
[1
1
1 ]
Let P = [−1 −1 1
1 0 1
0 1 1 ] and a non-singular matrix
Then,
AP = [3 2 2
2 3 2
2 2 3 ][−1 −1 1
1 0 1
0 1 1 ] = [ −1 −1 7
1 0 7
0 1 7 ]
PD = [−1 −1 1
1 0 1
0 1 1 ][1 0 0
0 1 0
0 0 1 ] = [−1 −1 7
1 0 7
0 1 7 ]
Given, A= [ 3 2 2
2 3 2
2 2 3 ]
The characteristic equation of A is, |3−x 2 2
2 3−x 2
2 2 3−x|x=0
i.e (3-x)*[(3−x)2−4] – 2*[6-2x-4] +2*[4-+2x] = 0
(3-x)*[5−6 x+ x2] + 8x -8 =0
x3 - 9x2 +15x -7 =0
(x−1)2 (X-7) = 0
X= 1, 1, 7
Thus the Eigenvalues of A are 1, 1, and 7 then the Eigenvectors are given as:
c
[
−1
1
0 ] +d [−1
0
1 ] Where c, d ≠ 0
The corresponding Eigenvector to the above Eigenvalue 7 is :
c
[1
1
1 ]
Let P = [−1 −1 1
1 0 1
0 1 1 ] and a non-singular matrix
Then,
AP = [3 2 2
2 3 2
2 2 3 ][−1 −1 1
1 0 1
0 1 1 ] = [ −1 −1 7
1 0 7
0 1 7 ]
PD = [−1 −1 1
1 0 1
0 1 1 ][1 0 0
0 1 0
0 0 1 ] = [−1 −1 7
1 0 7
0 1 7 ]
![Document Page](https://desklib.com/media/document/docfile/pages/linear-algebra-assignment-solutions/2024/09/08/ed03fdbe-2f2d-4f43-93e9-f9611abf4db1-page-13.webp)
ASSIGNMENT 13
Thus, AP = PD
i.e A= PDPT where P-1= PT
Question 5(b)
The maximum value of G(u)
G
[u1
u2
u3 ] = 3 ( u1
2+ u2
2+ u3
2 ) +3 (u1 u2+u2 u3 +u3 u1 )
u1
2 +u2
2 +u3
2
Then the maximum value of G(u) is at (-1,0,1), (0,-1,1), (-1,1,0),(1,0,-1),(1,-1,0),and (0,1,-1)
Thus, AP = PD
i.e A= PDPT where P-1= PT
Question 5(b)
The maximum value of G(u)
G
[u1
u2
u3 ] = 3 ( u1
2+ u2
2+ u3
2 ) +3 (u1 u2+u2 u3 +u3 u1 )
u1
2 +u2
2 +u3
2
Then the maximum value of G(u) is at (-1,0,1), (0,-1,1), (-1,1,0),(1,0,-1),(1,-1,0),and (0,1,-1)
1 out of 13
Related Documents
![[object Object]](/_next/image/?url=%2F_next%2Fstatic%2Fmedia%2Flogo.6d15ce61.png&w=640&q=75)
Your All-in-One AI-Powered Toolkit for Academic Success.
+13062052269
info@desklib.com
Available 24*7 on WhatsApp / Email
Unlock your academic potential
© 2024 | Zucol Services PVT LTD | All rights reserved.